Effect of Dry- and Wet-Milling Processes on Chemical, Physicochemical Properties and Starch Molecular Structures of Rice Starches - Anocha Suksomboon; Onanong Naivikul (Agriculture and Natural Resources, 2006)
Rice starches from low amylose (Pathum Thani 1), medium amylose (RD 7) and high amylose (Leuang 11) varieties prepared from dry- and wet-milling processes were investigated. Dry-milled rice starches contained significantly (p<0.05) higher amounts of damaged starch than wet-milled rice starches in all rice varieties. The scanning electron micrographs (SEM) of starch granules confirmed that damaged starches occurred from the dry-milling process more than from the wet-milling process. The enthalpy required to gelatinize dry-milled rice starches (8.11-9.53 J/g) from all rice varieties was significantly (p<0.05) lower than those of wet-milled rice starches (9.24-12.48 J/g). The peak viscosity (257.75-353.80 RVU) and final viscosity (248.64-391.00 RVU) of dry-milled rice starches measured by Rapid Visco Analyser (RVA) were significantly (p<0.05) lower than those of wet-milled rice starches. Rice starch molecular weight distributions obtained by size-exclusion chromatography with RI and multiangle laser light scattering detection (SEC-RI-MALLS) showed that dry-milled rice starch samples contained lower amounts of the high molecular weight portion of starch (amylopectin) than wet-milled samples. The molecular weight of both amylopectin from dry-milled rice starches (0.95-1.7 x 107 Da) was lower than that of wet-milled rice starches (1.11-1.90 x 107 Da), suggesting that the dry-milling process caused a higher degree of starch fragmentation than the wet-milling process.